2021
DOI: 10.1007/s10668-021-01974-0
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi optimization and life cycle assessment of biodiesel production from spent ground coffee

Abstract: In this study, Vietnamese spent coffee ground (SCG) were subjected to produce biodiesel for fuel application. The extraction processes were conducted with three organic solvents, i.e., hexane, petroleum ether and dimethyl ether. The extraction oil seems to be favored in hexane solvent (17.06%) as compared with petroleum ether (16.62%) and dimethyl ether (16.18%). The extraction processes tend to sufficiently follow the empirical hyperbolic model with R 2 of 0.973, 0.970 and 0.969 for hexane, petroleum ether, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The lowest ester content after IEE + TE could be influenced by the different molar ratio of MeOH/SCGO (8:1). Bui et al (2021) reported that the increase in the MeOH/SCGO ratio from 4:1 to 6:1 resulted in an increase transesterification yield, which was, however, reduced with further increase of the MeOH/SCGO ratio [62]. Additionally, the lower unidentified matter was observed in the sample of final biodiesel after AE + TE.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…The lowest ester content after IEE + TE could be influenced by the different molar ratio of MeOH/SCGO (8:1). Bui et al (2021) reported that the increase in the MeOH/SCGO ratio from 4:1 to 6:1 resulted in an increase transesterification yield, which was, however, reduced with further increase of the MeOH/SCGO ratio [62]. Additionally, the lower unidentified matter was observed in the sample of final biodiesel after AE + TE.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…Following this, the dehydrated SCG wastes are treated with solvents like hexane or toluene to remove their lipid fraction (Fehse et al, 2021;Tongcumpou et al, 2019;Setter et al, 2020), which later on can be used in the production of SCG oil biodiesel (Bui et al, 2022). In general, these wastes are refluxed with these solvents for 4-6 hours, at temperatures maintained slightly above the corresponding boiling point of the solvent used; and are treated in a Soxhlet extractor for lab scale studies.…”
Section: Pre-treatment and Processing Of Scg Wastesmentioning
confidence: 99%